Mitigating climatic changes for sustainable coconut production - Hebbar, K B (Indian Horticulture, 2018)
Coconut plantation during the last 3-4 years is facing the severe threat of climate change in Karnataka, Tamil Nadu, Kerala and Andhra Pradesh, the major coconut-growing states. Lakhs of coconut trees withered during summer seasons of 2013 and 2014 in south interior Karnataka due to scanty rainfall. Almost similar fatality happened in some districts of Tamil Nadu. During summer of 2016, vast tracts of coconut withered in northern Kerala due to extended drought. Though some trees recover with the arrival of monsoon but the production will be affected at least for 3 years. On the other hand in the east coast of Andhra Pradesh and Orissa, a large number of trees were uprooted due to cyclones. In 2015, all along the west coast, plants had scorching of leaves due to salt spray effect. On the top of all this, temperature has been increasing and rainfall decreasing significantly since 1980s in tune with the global warming especially across the high ranges, followed by the low lands where coconut is predominantly grown. Therefore sustainable production approaches are required for adapting to new climates.